Indonesian Students’ Growth Perception of an English Immersion Program - Pratiwi, Widya Rizky (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Becoming a part of an English village as a form of immersion program differs significantly from studying English in a classroom setting where students can directly practice speaking in real-life situations. This study looks at how Indonesian students perceive the benefits of intense classes in an English Immersion ProgramÂ on their cognitive development both during and after the program. The biggest Indonesian English Village, Kampung Inggris Pare, was the location. This qualitative case study involving participant observation, interviews, and photos included 14 participants. An interactive analytic model was then used to gather, reduce, present, and make conclusions from the data. According to the study, most participants improvedÂ after taking intense English classes in Kampung Inggris Pare, especially in the cognitive areas. Vocabulary was the area where they felt most Heavily Upgraded (HUg), followed by fluency and pronunciation. This study suggests that an immersion program like English Village is one way to address several issues with English learning in schools. An English Immersion Program's intense sessions might be advantageous for students.